Adjuvant vemurafenib in resected, BRAFV600 mutation-positive melanoma (BRIM8): a randomised, double-blind, placebo-controlled, multicentre, phase 3 trial. Issue 4 (April 2018) - Maio, Michele; Lewis, Karl; Demidov, Lev; Mandalà, Mario; Bondarenko, Igor; Ascierto, Paolo A; Herbert, Christopher; Mackiewicz, Andrzej; Rutkowski, Piotr; Guminski, Alexander; Goodman, Grant R; Simmons, Brian; et al.
Summary: Background: Systemic adjuvant treatment might mitigate the high risk of disease recurrence in patients with resected stage IIC–III melanoma. The BRIM8 study evaluated adjuvant vemurafenib monotherapy in patients with resected, BRAF V600 mutation-positive melanoma. Methods: BRIM8 was a phase 3, international, double-blind, randomised, placebo-controlled study that enrolled 498 adults (aged ≥18 years) with histologically confirmed stage IIC–IIIA–IIIB (cohort 1) or stage IIIC (cohort 2) BRAF V600 mutation-positive melanoma that was fully resected. Patients were randomly assigned (1:1) by an interactive voice or web response system to receive twice-daily adjuvant oral vemurafenib 960 mg tablets or matching placebo for 52 weeks (13 × 28-day cycles). Randomisation was done by permuted blocks (block size 6) and was stratified by pathological stage and region in cohort 1 and by region in cohort 2. The investigators, patients, and sponsor were masked to treatment assignment. The primary endpoint was disease-free survival in the intention-to-treat population, evaluated separately in each cohort. Hierarchical analysis of cohort 2 before cohort 1 was prespecified. This trial is registered withClinicalTrials.gov, numberNCT01667419 . Findings: The study enrolled 184 patients in cohort 2 (93 were assigned to vemurafenib and 91 to placebo) and 314 patients in cohort 1 (157 were assigned to vemurafenib and 157 to placebo). At the time of data cutoff (April 17, 2017), median study follow-up was 33·5 months (IQR 25·9–41·6) in cohort 2 and 30·8 months (25·5–40·7) in cohort 1. In cohort 2 (patients with stage IIIC disease), median disease-free survival was 23·1 months (95% CI 18·6–26·5) in the vemurafenib group versus 15·4 months (11·1–35·9) in the placebo group (hazard ratio [HR] 0·80, 95% CI 0·54–1·18; log-rank p=0·026). In cohort 1 (patients with stage IIC–IIIA–IIIB disease) median disease-free survival was not reached (95% CI not estimable) in the vemurafenib group versus 36·9 months (21·4–not estimable) in the placebo group (HR 0·54 [95% CI 0·37–0·78]; log-rank p=0·0010); however, the result was not significant because of the prespecified hierarchical prerequisite for the primary disease-free survival analysis of cohort 2 to show a significant disease-free survival benefit. Grade 3–4 adverse events occurred in 141 (57%) of 247 patients in the vemurafenib group and 37 (15%) of 247 patients in the placebo group. The most common grade 3–4 adverse events in the vemurafenib group were keratoacanthoma (24 [10%] of 247 patients), arthralgia (17 [7%]), squamous cell carcinoma (17 [7%]), rash (14 [6%]), and elevated alanine aminotransferase (14 [6%]), although all keratoacanthoma events and most squamous cell carcinoma events were by default graded as grade 3. In the placebo group, grade 3–4 adverse events did not exceed 2% for any of the reported terms. Serious adverse events were reported in 40 (16%) of 247 patients in the vemurafenib group and 25 (10%) of 247 patients in the placebo group. The most common serious adverse event was basal cell carcinoma, which was reported in eight (3%) patients in each group. One patient in the vemurafenib group of cohort 2 died 2 months after admission to hospital for grade 3 hypertension; however, this death was not considered to be related to the study drug. Interpretation: The primary endpoint of disease-free survival was not met in cohort 2, and therefore the analysis of cohort 1 showing a numerical benefit in disease-free survival with vemurafenib versus placebo in patients with resected stage IIC–IIIA–IIIB BRAF V600 mutation-positive melanoma must be considered exploratory only. 1 year of adjuvant vemurafenib was well tolerated, but might not be an optimal treatment regimen in this patient population. Funding: F Hoffman–La Roche Ltd.